The Models of Auto-Confessional Author - Gashi, Agron Y. (Journal of History Culture and Art Research, 2021)
A discussion that used a theoretical discourse as opposed to the discourse used by positivism began in the second half of the past century with the focus on the issue of the author in literature. The search for the author by the method of looking for him/her in between the lines was evident in literary theories, especially after Roland Barthes’ eminent essay The Death of the Author (written in 1968). Afterwards, the issue of the author was regarded by European and Anglo-American schools as an issue to be discovered within the text either as the presence of the narrator or the author, or as an explicit presence as an auto-confessional author. Being of such an explicit nature, it is not unexpected that the auto-confessional author has oftentimes been neglected. Upon this consideration, the auto-confessional author is the object of this paper that aims to set about a theoretical and conceptual confrontation with the purpose of framing a model of the auto-confessional author and his manifestation in literature.